Russia's Financial Markets Boom, Crisis and Recovery 1995-2001: Lessons for Emerging Markets Investors - Ralph Süppel (SUERF - The European Money and Finance Forum, 2003)
From 1995 to 2001 Russia witnessed an asset market boom, a deep financial crisis, and a surprisingly forceful recovery. An event study of this episode provides important insights for Emerging Market investment and Russia's medium-term prospects. The initial surge in bond and stock prices in 1995-97 owed to a highly ambitious monetary stabilization program, which compressed inflation much faster than other transition economies. Due to high dollarization, disinflation was based on the exchange rate. The program produced rapid real appreciation and a persistent need for capital inflows, while weak economic structures and lack of domestic political support prevented accompanying fiscal consolidation and foreign direct investment. The gap between stabilization ambition and structural reality made the currency increasingly vulnerable. Also, the program did not provide a politically viable "emergency exit" from the exchange rate target corridor. Devaluation was postponed through heavy international support. The ultimate crisis escalation in August 1998 resulted in a partial government default and steep devaluation. However, the economy responded from 1999 with relief to the real depreciation, entering a phase of sustained expansion. Also, the crisis escalation united the political spectrum around a new fundamental consensus on economic policy. Post-crisis governments prioritized fiscal consolidation over disinflation. The more stable political and economic environment spurred broader economic reform from 2000, particularly in the areas of public finances and investment conditions. Together with persistent commitment towards international integration this heralds a long-term convergence of Russia's economic structures with those in Central and Western Europe.
Keywords: E44; E65; F31; F34; 330; Russia; Transition Economies; Emerging Markets; Financial Crisis; Debt Restructuring; Finanzmarkt; Geldpolitik; Wechselkurspolitik; Wirtschaftsreform; Finanzpolitik; Russland; Finanzkrise